Revolutionizing Transportation: Exploring Yassir App's Features, Challenges, And User Insights - Salhi Nadia (جامعة الوادي University of Eloued, 2024)
This article delves into the Yassir app's transport features, challenges, and applications, with a specific focus on its case study and sample study users. Yassir, a popular transportation solution, has transformed commuting by offering convenience and accessibility. The case study highlights its impact on traditional transportation methods, emphasizing affordability and user convenience. Additionally, the article conducts a sample study of Yassir app users, revealing insights into their preferences and experiences. Through this research, the article provides a comprehensive view of how Yassir has revolutionized transportation and adapted to users' evolving needs. This analysis contributes to understanding the potential and limitations of app-based transport solutions in modern urban contexts Cet article explore les fonctionnalités de transport de l'application Yassir, ses défis et ses applications en se concentrant particulièrement sur son étude de cas et ses types utilisateurs. Yassir, une solution de transport populaire, a transformé les déplacements en offrant praticité et accessibilité. L'étude de cas met en évidence son impact sur les méthodes de transport traditionnelles, en insistant sur l'abordabilité et la commodité pour les utilisateurs. De plus, l'article mène une étude d'échantillon des utilisateurs de l'application Yassir, révélant des insights sur leurs préférences et expériences. À travers cette recherche, l'article offre une vue d'ensemble de la manière dont Yassir a révolutionné les transports et s'est adapté aux besoins en constante évolution des utilisateurs. Cette analyse contribue à la compréhension du potentiel et des limites des solutions de transport basées sur les applications dans les contextes urbains modernes.
Keywords: yassir app; ride-hailing apps; urban transportation; Uber; Yassir